2020
DOI: 10.1111/ceo.13829
|View full text |Cite
|
Sign up to set email alerts
|

Switchover study of onabotulinumtoxinA to incobotulinumtoxinA for facial dystonia

Abstract: Importance When making a cost‐saving it is important to ensure there is no loss of efficacy. Background Clinical effectiveness and efficiency of incobotulinumtoxinA compared to onabotulinumtoxinA in facial dystonia is unclear. Our aim is to evaluate switching from onabotulinumtoxinA to incobotulinumtoxinA in the treatment of essential blepharospasm (EB), hemifacial spasm (HFS) and aberrant facial nerve regeneration (AFR). Design A retrospective study of a prospective, single‐masked switchover audit from onabot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Inco seemed to have a slightly higher subjective improvement and longer duration of the effect compared to Ona. However, the study included a small number (=12) of patients [62]. A prospective, randomized, double-blind study comparing Lan and Ona reported that these formulations had similar efficacies (mean duration effect: 12.8 vs. 12.9, respectively), no significant difference in safety, along with similar tolerability profiles (excellent for 25.5% Ona and 5.3% Lan, good for 64.7% Ona and 57.9% Lan), so that a dose equivalence of 1:1 may be considered for HFS treatment [60].…”
Section: Reported Trials-evidence-based Medicinementioning
confidence: 99%
“…Inco seemed to have a slightly higher subjective improvement and longer duration of the effect compared to Ona. However, the study included a small number (=12) of patients [62]. A prospective, randomized, double-blind study comparing Lan and Ona reported that these formulations had similar efficacies (mean duration effect: 12.8 vs. 12.9, respectively), no significant difference in safety, along with similar tolerability profiles (excellent for 25.5% Ona and 5.3% Lan, good for 64.7% Ona and 57.9% Lan), so that a dose equivalence of 1:1 may be considered for HFS treatment [60].…”
Section: Reported Trials-evidence-based Medicinementioning
confidence: 99%